2017
DOI: 10.1080/02813432.2017.1397246
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems and changes in drug utilization after medication reviews in nursing homes in Oslo, Norway

Abstract: ObjectiveWe describe the drug-related problems (DRPs) identified during medication reviews (MRs) and the changes in drug utilization after MRs at nursing homes in Oslo, Norway. We explored predictors for the observed changes.DesignObservational before-after study.SettingForty-one nursing homes.InterventionMRs performed by multidisciplinary teams during November 2011 to February 2014.SubjectsIn all, 2465 long-term care patients.Main outcome measuresDRPs identified by explicit criteria (STOPP/START and NORGEP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 25 publications
2
62
3
3
Order By: Relevance
“…Many of the people with dementia in nursing homes have other chronic disorders in addition to dementia, and inappropriately prescribed medications have been a challenge in Norwegian nursing home residents (Halvorsen, Selbaek, & Ruths, 2017). A recent study described that a Norwegian nursing home resident on average used 6.8 different drugs on daily basis, and about 83% of the nursing home residents have, on average three drug-related problems (Fog, Kvalvaag, Engedal, & Straand, 2017). The authors found that use of inappropriate drugs, high dosages, and lack of drug use monitoring were some of the most frequent drug-related problems.…”
Section: Norwegian Nursing Homesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the people with dementia in nursing homes have other chronic disorders in addition to dementia, and inappropriately prescribed medications have been a challenge in Norwegian nursing home residents (Halvorsen, Selbaek, & Ruths, 2017). A recent study described that a Norwegian nursing home resident on average used 6.8 different drugs on daily basis, and about 83% of the nursing home residents have, on average three drug-related problems (Fog, Kvalvaag, Engedal, & Straand, 2017). The authors found that use of inappropriate drugs, high dosages, and lack of drug use monitoring were some of the most frequent drug-related problems.…”
Section: Norwegian Nursing Homesmentioning
confidence: 99%
“…The authors found that use of inappropriate drugs, high dosages, and lack of drug use monitoring were some of the most frequent drug-related problems. Use of psychotropic drugs and opioids were involved in most of the drug-related problems among nursing home residents (Fog et al, 2017). Another Norwegian study reported that 69% of nursing home residents receive one or more psychotropic medications;…”
Section: Norwegian Nursing Homesmentioning
confidence: 99%
“…There were no reports as to the reasons underlying why PRN medications were prescribed and administered, but the absence of guidelines, and information as to the side effects and adverse drug reactions and "what to look out for" was notable. The use of unnecessary medications, excess dosing, and lack of monitoring in terms of medications' effects and side effects have been highlighted as the most frequent medication-related problems, particularly for psychotropic medications [27,45]. Appropriate medication prescription for residents living in long-term care settings is a challenge for healthcare systems across the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Flere studier av legemiddelbruk i norske sykehjem har vist at en stor andel av beboerne får antipsykotiske legemidler (10,12,13), men en nyere sykehjemsstudie har vist at det er redusert bruk av antipsykotika ved demens (14).…”
Section: Fortolkningunclassified